2018
DOI: 10.1016/j.jjcc.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Progression of pulmonary artery dilatation in patients with pulmonary hypertension coexisting with a pulmonary artery aneurysm

Abstract: PA dilatation progressed in patients with a PA aneurysm despite treatment of PH. The progression of PA dilatation is independent of reduction of PA pressure by PH treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 18 publications
(20 reference statements)
0
19
0
Order By: Relevance
“…Other case report of 65-year-old patient with proximal PAA and PH which had been treated conservatively with intravenous epoprostenol showed that after 20 months of treatment, pulmonary artery pressure was nearly normalized and the size of PAA remains the same [18]. However, recent studies found that the progression of PAA dilatation is independent of the change in pulmonary artery pressure [19,20]. We argue that the difference between our findings or the previous case reports and the previous cohort studies was because of the difference in the follow-up period.…”
Section: A B Cmentioning
confidence: 99%
“…Other case report of 65-year-old patient with proximal PAA and PH which had been treated conservatively with intravenous epoprostenol showed that after 20 months of treatment, pulmonary artery pressure was nearly normalized and the size of PAA remains the same [18]. However, recent studies found that the progression of PAA dilatation is independent of the change in pulmonary artery pressure [19,20]. We argue that the difference between our findings or the previous case reports and the previous cohort studies was because of the difference in the follow-up period.…”
Section: A B Cmentioning
confidence: 99%
“…However, despite PAA being common among PAH patients, hemodynamic severity of PAH has not shown to be an independent risk factor for PAA development in this population [1]. Furthermore, effective PA pressure reduction with pulmonary vasodilators have failed to stop progressive PA enlargement [2,7]. Thus, it seems that a chronic exposure to an increased afterload worsen irreversible ECM changes leading to PA growth [1].…”
Section: Hemodynamic Overload Contributes To Development Of Both Aortmentioning
confidence: 99%
“…However, not every patient exposed to an increased intravascular pressure develops a great vessel aneurysm. Furthermore, the effect of antihypertensive drugs or pulmonary vasodilators on artery diameter change is debatable [2,7]. Thus, besides increased intravascular pressure, patients who finally develop abnormal artery growth must present a genetic susceptibility triggering ECM changes responsible of aneurysm development.…”
Section: Hemodynamic Overload Contributes To Development Of Both Aortmentioning
confidence: 99%
See 1 more Smart Citation
“…Aneurysm and pseudoaneurysm are uncommon, but potentially life-threatening abnormalities of the pulmonary arteries. Aneurysm of the main pulmonary artery (MPA) defined as MPA diameter over 40 mm was reported in 1 : 14 000 autopsies [1,2]. By definition, an aneurysm is a local dilatation of a blood vessel, involving all three layers of the vessel wall: the tunica intima, tunica media, tunica adventitia [3].…”
Section: Introductionmentioning
confidence: 99%